The Influence of Digital Marketing, Price, and Service Quality on Consumer Buying Interest (At the Smoked Fish Processing Center in Wonosari Village, Demak District) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze and demonstrate the influence of digital marketing, price, and service quality on purchase intention among consumers at a smoked fish processing center in Wonosari Village, Demak Regency. Respondents in this study were 97 consumers at a smoked fish processing center in Wonosari Village, Demak Regency. Data collection was conducted by distributing questionnaires. This study employed quantitative methods using Google Forms. The results of this study indicate a positive and significant effect of digital marketing on purchase intention, price on purchase intention, and service quality on purchase intention. Meanwhile, the F-test showed a significant positive effect between digital marketing (X1), price (X2), and service quality (X3) on purchase intention (Y).
Keywords: Digital Marketing; Price, Service Quality; Purchase Intention